Perpindahan Hak Hadhanah Pasca Perceraian (Analisis Putusan Mahkamah Agung Nomor 406K/AG/2016) - Mardiyah, Siti; Elfia (Fakultas Agama Islam UNISMA, 2024)
Based on general provisions, mothers are more entitled to have hadhanah rights for children who are not yet mumayyiz. However, in Supreme Court Decision Number 406K/AG/2016, the judge decided to transfer the hadhanah rights for children who have not yet mumayyiz from the mother's side to the father's side. This makes the Supreme Court's decision a Contra Legem decision which is not based on formal legal normative rules. So the aim of this research is (1) to analyze the considerations of the panel of judges in the Supreme Court decision number 406K/AG/2016 (2) to a nalyze the decision from the perspective of maslahah murlah. The research method used is normative juridical, namely legal research by reviewing library materials or secondary data. The results of this research: (1) The judge's considerations in deciding the case are based on the welfare and best interests of the child. (2) Even though the Supreme Court Decision Number 406K/AG/2016 is contra legem, the decision aims to eliminate harm and create benefits, from a fiqh perspective this does not conflict with the rules of Maqashid syari’ah . Keywords: Hadhanah, Putusan Mahkamah Agung, Maslahah Mursalah